ANALISIS PERBANDINGAN EFISIENSI BIAYA DAN EFEKTIFITAS WAKTU PELAKSANAAN LAPIS PONDASI BAWAH ANTARA AGREGAT KELAS B DAN BETON KURUS (Jurnal Spesialis Teknik Sipil (JSpTS), 2019)
Debate both technically and economically in the use of road construction used often occurs.One of them is the lower foundation layer as a working floor and transfer of load from the topcover layer to the subgrade. The purpose of this study was to obtain the level of technicaleffectiveness and the level of cost and time efficiency in the use of thin concrete and aggregategrade foundation layers from the Mangkurawang-Rapak Lambur road improvement projectin Tenggarong District. Rigid hardening is determined as the closing pavement. Technicallythe pavement plan design uses the 1993 AASHTO method while the 2017 binary analysismethod is used to compare costs and time. The results show that for a road improvementproject of 1,151 km with a subgrade CBR of 5%, the lower grade aggregate foundation B is15 cm thick with a planned budget of Rp. 5,153,245,000.00 while the time required is 49 days.Meanwhile for thin concrete 10 cm thick. With a budget plan of Rp. 6,147,623,000.00 within43 days. Means the bottom foundation layer aggregate class B 16.18% more efficient with atime of 12.24% more efficiency compared to thin concrete.Keywords: lower foundation layer, thin concrete, AASHTO, binamarga analysis